2003
DOI: 10.1109/tmag.2003.816271
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic properties, magnetic cluster size, and read-write performance of CoPtCr-SiO/sub 2/ perpendicular recording media

Abstract: The characteristics of CoPtCr-SiO 2 perpendicular media were investigated, especially focusing on the dependence of magnetic properties and read-write performance on magnetic cluster size.increases with reducing magnetic cluster size. As magnetic cluster size decreases, media noise and signal-to-noise ratio are improved and magnetic write width becomes narrower, indicating that reducing the magnetic cluster size is an effective means to increase both bit and track densities. However, diminution of magnetic clu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…The domain size was measured as follows. It is based on a method of measuring domain size by approximating magnetic domain shape with a circle [10]. As shown in Fig.…”
Section: Domain Size Distributionmentioning
confidence: 99%
“…The domain size was measured as follows. It is based on a method of measuring domain size by approximating magnetic domain shape with a circle [10]. As shown in Fig.…”
Section: Domain Size Distributionmentioning
confidence: 99%
“…Previous works on CoPtCr-SiO 2 media deposited on a Ru underlayer showed that exchange coupling can be varied depending on the thickness or deposition condition of the Ru underlayer [4,7]. In this work, the exchange was systematically varied by controlling the Cr-O grain boundary segregation.…”
Section: Introductionmentioning
confidence: 96%
“…Since large magnetic domains cause a considerable amount of medium noise, it is necessary to decrease the intergranular exchange interaction in order to apply SmCo 5 thin films to practical media [17,18].…”
Section: Introductionmentioning
confidence: 99%